The Effect of Social Media on Students’ Motivation in Reading Printed Materials - Siti Nurul Ilmi HL (Universitas Negeri Makassar, 2022)
There is tendency that today's students are less interested in reading books and more likely to rely on other forms of passive media (movies, TV shows, Internet, etc.) for their information needs. The purpose of this research is to investigate whether or not students' increasing use of digital technologies, particularly social media, has affected their motivation for reading printed texts. A total of 80 students from three schools in Bone regency are surveyed for this study. The data demonstrates that students in senior high school in Bone regency spend more time-consuming digital media than they do reading traditional print materials. As opposed to reading a book, they enjoy using technology or interacting on social media. Therefore, the purpose of this research is to highlight the students’ motivation of reading printed materials in senior high schools in Bone regency.